НАУКОВІ ОСНОВИ ІНТЕГРАЦІЇ ЯК ОДНІЄЇ З ТЕНДЕНЦІЙ РОЗВИТКУ СУЧАСНОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2022)
The article has made an attempt to define the scientific grounds of integration, to give a broad online its potential in terms o f the teaching process in modern school